Spontaneous Pulmonary Lobe Torsion in an Elderly Pug - Treatment with Total Lobectomy by Videoassisted Thoracic Surgery (VATS) - Schiefler, Otávio Henrique de Melo; Caye, Pâmela; Antunes, Bernardo Nascimento; Engelsdorff, João Segura; Gasparotto, Jean Carlos; Pozzobon, Francieli Mallmann; Marcus, Valentina Berté; Brun, Maurício Veloso (Acta Scientiae Veterinariae, 2024)
Background: Spontaneous pulmonary lobe torsion is a rare condition in small dogs. We highlight the use of video-ssisted thoracic surgery (VATS) to treat this disease, once it has shown several benefits compared to conventional open surgery, even if there are few reports in veterinary medicine. The minimally invasive surgical modality has been gaining great interest and prominence due to its applicability, less tissue trauma, lower consumption of analgesics and rapid post-operative recovery. The aim of this paper is to report a case of total pulmonary lobectomy due to spontaneous torsion of the left cranial pulmonary lobe performed using the minimally invasive VATS method. Case: A 11-year-old male neutered Pug was referred to the University Veterinary Hospital of UFSM with a history of progressive cough, dyspnea and epistaxis for 1 year and getting worse in the last 6 months. The radiographic and ultrasonographic chest exams revealed consolidation and pleural effusion in the left cranial hemithorax. The suspect of pulmonary lobe torsion was confirmed by video-assisted thoracic surgery (VATS), were the cranial portion of the pulmonary lobe and part of the caudal portion was compromised. As a therapeutic method, total video-assisted pulmonary lobectomy was performed. During the procedure low nociceptive stimuli were observed and no complication occurred, also after the operation. The clinical signs of coughing and difficulty breathing were solved and the patient was discharged from hospital approximately 24 h after the procedure. Discussion: Pulmonary lobe torsion (PLT) has a higher prevalence in medium and large dogs with narrow and deep chest, but Pugs are reported to be the most small breed susceptible to developing PLT. Secondary factors are commonly involved, such as trauma and chronic respiratory diseases and it can also occur after surgical procedures. It rarely occurs spontaneously. The median age in this breed is usually between 1.5 and 7-year-old. As this condition have potential to cause thoracic hemorrhage, thrombosis and tissue necrosis, treatment consists of removing the affected lung lobe by total pulmonary lobectomy. The video-assisted method for treating PLT has not been reported in dogs yet. Minimally invasive procedures such as VATS have been increasingly used in veterinary medicine as they allow surgical access to the cavity through small incisions without compromising surgical exposure and the quality of the procedure, resulting in less tissue trauma, less surgical stress, less analgesic consumption and a shorter hospitalization compared to conventional thoracotomies. Through 2 small surgical incisions of approximately 6 mm to insert the portals, it was possible to quickly identify the compromised left cranial lung lobe and the involvement of the caudal lung lobe. Minimally invasive accesses and little tissue manipulation allowed that the total pulmonary lobectomy procedure was carried out effectively and with little trauma, enabling the patient to be discharged from hospital 1 day after the procedure. In conclusion, VATS proved to be an effective diagnostic and therapeutic tool in TLP with less manipulation and tissue damage. Keywords: minimally invasive surgery, thoracoscopy, video surgery, lung lobectomy. Título: Torção espontânea de lobo pulmonar em um Pug idoso - tratamento com lobectomia total via cirurgia torácica vídeo-assistida (CTVA) Descritores: cirurgia minimamente invasiva, toracoscopia, videocirurgia, lobectomia pulmonar.